PENGARUH SENAM HAMIL DALAM MENGATASI NYERI PUNGGUNG PADA IBU HAMIL - Yuli, Yuli fransiska; Linda Suryani (Universitas Batam, 2024)
Back pain in pregnant women is caused by hormonal changes in the supporting and connecting soft tissues, which results in reduced muscle flexibility. Management to reduce back pain is to maintain good posture by paying attention to the body's mechanisms during pregnancy exercises. The aim of this research is to determine the effect of pregnancy exercise in treating back pain in pregnant women. The research method used is quantitative with Quasi Experimental Design in the form of a one group pretest-posttest method. The sample for this study consisted of 51 pregnant women with a gestational age of > 24 weeks who were selected using a random sampling technique. Data analysis used the Wilcoxon test. The results of the research before being given the pregnancy exercise intervention were 28 people (54.9%) experiencing moderate back pain and 23 people (45.1%) experiencing severe back pain. After being given the pregnancy exercise intervention, 31 people (60.8%) experienced mild back pain and 20 people (39.2%) experienced moderate back pain. The results of statistical tests using the Wilcoxon test obtained a ρ-value of 0.000 so it can be concluded that there is an influence of pregnancy exercise in overcoming back pain in pregnant women. The advice given by this research is to implement a structured and regularly scheduled pregnancy exercise program. This can help reduce back pain and improve the well-being of pregnant women.